Optimalkan Pelayanan Kesehatan Masyarakat: Pemahaman Mendalam Tentang Rekam Medis Elektronik Bagi Petugas Rekam Medis Di Puskesmas Tabunganen - Soraya, Soraya; Asih, Hastin Atas; Auliani, Firda; Istiqamah, Nur (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
This community service aims to optimize healthcare services by enhancing the knowledge of medical record officers at Puskesmas Tabunganen regarding electronic medical records. In order to achieve this goal, a profound understanding of EMR becomes a crucial key, particularly for medical record officers. By comprehensively understanding the concepts and implementation of EMR, medical record officers at Puskesmas Tabunganen are expected to improve the efficiency of health data management. This community service makes a positive contribution to preparing the health center for the implementation of electronic medical records. This community service has a positive impact on preparing Puskesmas Tabunganen for the implementation of electronic medical records.